2013
DOI: 10.1136/annrheumdis-2013-204145
|View full text |Cite
|
Sign up to set email alerts
|

Fish oil in recent onset rheumatoid arthritis: a randomised, double-blind controlled trial within algorithm-based drug use

Abstract: BackgroundThe effects of fish oil (FO) in rheumatoid arthritis (RA) have not been examined in the context of contemporary treatment of early RA. This study examined the effects of high versus low dose FO in early RA employing a ‘treat-to-target’ protocol of combination disease-modifying anti-rheumatic drugs (DMARDs).MethodsPatients with RA <12 months’ duration and who were DMARD-naïve were enrolled and randomised 2:1 to FO at a high dose or low dose (for masking). These groups, designated FO and control, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
86
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 137 publications
(89 citation statements)
references
References 25 publications
0
86
0
3
Order By: Relevance
“…Eskimos consuming large amounts of fish oil report a lower incidence of RA [46]. In a recent double-blind controlled study, RA patients treated with 5.5 g of n-3 PUFAs/day showed reduced treatment failure and a higher rate of achievement of disease remission [47]. The question of whether the ratio of n-6/n-3 PUFAs or total amount of dietary n-3 PUFA intake is of great concern.…”
Section: Discussionmentioning
confidence: 99%
“…Eskimos consuming large amounts of fish oil report a lower incidence of RA [46]. In a recent double-blind controlled study, RA patients treated with 5.5 g of n-3 PUFAs/day showed reduced treatment failure and a higher rate of achievement of disease remission [47]. The question of whether the ratio of n-6/n-3 PUFAs or total amount of dietary n-3 PUFA intake is of great concern.…”
Section: Discussionmentioning
confidence: 99%
“…Beneficial effects continue to be seen when fish oil is added to triple DMARD therapy with a treat-to-target approach in early RA. 26 In this study we sought to determine whether plasma levels of n-3 fatty acids correlated with response to anti-TNF in RA, and propose and test a mechanistic hypothesis for the heightened responsiveness we observed in association with higher EPA levels in the absence of high dose fish oil supplementation.…”
Section: Introductionmentioning
confidence: 99%
“…Although NSAIDs transiently reduce knee OA pain, due to the adverse effects, American College of Rheumatology (ACR) guidelines recommend intermittent use only 2. A systematic review of fish oil use in rheumatoid arthritis (RA) reported decreased NSAID use with fish oil,3 and a randomised controlled trial (RCT) of high-dose fish oil in recent-onset RA demonstrated a higher remission rate 4. Synovial inflammation is associated with severity of pain in knee OA5–7 and has been variably associated with cartilage loss 7 8.…”
Section: Introductionmentioning
confidence: 99%